Desain dan Implementasi Data Warehouse Penjualan Pada Database Sample Northwind Menggunakan Tools Tableau - Sentana, I Putu Bagus Merta; Dwidasmara, Ida Bagus Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Many corporate is using data warehouse as a place to store the operational data that has a purpose to support analytical and business decision making processes. Data warehouse have an ability to integrate and analyze data which are considered complex in order to support the analytical process and business decision-making of a company. The study will conduct a design and implementation of the data warehouse which uses the Northwind Database Sample as its main data sources. The process of designing the data warehouse, will use a methodology called Nine Step Design Methodology and Tableau desktop as its software to implement and visualize the data warehouse  itself.